Community Sovereignty as A Regulatory Membrane: Governing Systemic Vitality in Regenerative Tourism Destinations - IGW Suyasa; Diah Suryandari; Erik Susanto; Sugiarto (Riviera Publishing, 2026)
Regenerative tourism has emerged as a transformative paradigm capable of addressing the structural limitations of sustainable tourism by repositioning destinations as living social–ecological systems. Consequently, regeneration is often framed as an aspirational outcome rather than as a governed systemic condition. This article argues that the transformative potential of regenerative tourism cannot be realized without addressing the issue of structural regulation. Drawing on living systems thinking and political economy perspectives, this paper introduces community sovereignty as a regulatory membrane that governs selective permeability within a destination’s metabolic system. Employing a conceptual theory-building approach, this study develops an integrative analytical framework that reconceptualizes destination governance as an active process of metabolic regulation rather than merely a coordinative arrangement. The framework identifies four key regulatory dimensions—collective decision-making authority, institutional coherence, normative orientation, and adaptive enforcement capacity—which collectively determine the quality and intensity of tourism flows. These theoretical propositions are empirically illustrated through analytical vignettes that contrast the extractive tendencies of highly permeable systems with the sovereign regulatory architecture of the Binyan Customary Forest (Hutan Adat Binyan) (Wanaprastha) in Bali. This article contributes to regenerative tourism scholarship by shifting the analytical focus from participation toward regulatory capacity and by reframing governance as an active practice of boundary-setting. Ultimately, this framework provides a robust foundation for analyzing systemic vitality as a governable condition amid intensifying global tourism pressures.